Schizophrenia: Developmental Variability Interacts with Risk Factors to Cause the Disorder: Nonspecific Variability‐Enhancing Factors Combine with Specific Risk Factors to Cause Schizophrenia. (31st August 2020) - Szoke, Andrei; Pignon, Baptiste; Boster, Sarah; Jamain, Stéphane; Schürhoff, Franck
Abstract: A new etiological model is proposed for schizophrenia that combines variability‐enhancing nonspecific factors acting during development with more specific risk factors. This model is better suited than the current etiological models of schizophrenia, based on the risk factors paradigm, for predicting and/or explaining several important findings about schizophrenia: high co‐morbidity rates, low specificity of many risk factors, and persistence in the population of the associated genetic polymorphisms. Compared with similar models, e.g., de‐canalization, common psychopathology factor, sexual‐selection, or differential sensitivity to the environment, this proposal is more general and integrative. Recently developed research methods have proven the existence of genetic and environmental factors that enhance developmental variability. Applying such methods to newly collected or already available data can allow for testing the hypotheses upon which this model is built. If validated, this model may change the understanding of the etiology of schizophrenia, the research models, and preventionbrk paradigms. Abstract : Risk factors specifically enhance the probability of adverse/negative outcomes (red), e.g., schizophrenia. Opportunity factors increase the probability of favorable/positive outcomes (blue), e.g., exceptional achievement. Variability factors interact with risk or opportunity factors and nonspecifically enhance the probability of extreme outcomes both positive and negative.